2023
DOI: 10.1093/ofid/ofad103
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mortality Associated With Loiasis: Confirmation by a New Retrospective Cohort Study Conducted in the Republic of Congo

Abstract: Background Loiasis (Loa loa filariasis) is considered a benign disease and is currently not included in the WHO’s list of Neglected Tropical Diseases, despite mounting evidence suggesting significant disease burden in endemic areas. We conducted a retrospective cohort study to assess the mortality associated with L. loa microfilaremia in southwestern Republic of Congo. Methods The cohort included 3329 individuals from 53 vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…loa mfs in the blood is associated with excess mortality and the risk of premature death is proportionally associated with the L . loa MFD, but the causes of this excess mortality remain unidentified [ 4 , 5 ]. The possible development of arterial stiffness as a consequence of L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…loa mfs in the blood is associated with excess mortality and the risk of premature death is proportionally associated with the L . loa MFD, but the causes of this excess mortality remain unidentified [ 4 , 5 ]. The possible development of arterial stiffness as a consequence of L .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two retrospective population-based cohort studies demonstrated that people with high L . loa MFD have a significantly reduced life expectancy and that the risk of premature death is proportional to an individual’s MFD [ 4 , 5 ]. Reasons for this excess mortality are still unknown and are probably multifactorial but cardiovascular diseases (CVD) could be one of the causes.…”
Section: Introductionmentioning
confidence: 99%
“…Yet some individuals may still have been misclassified as amicrofilaremic. Importantly, excess mortality and morbidity have been associated with any detectable L. loa microfilaremia [3,6,13,32]. Thus, identification of all microfilaremic patients is an important objective of loiasis diagnostics.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…However, health care professionals working on loiasis have repeatedly advocated for loiasis-centered research. This call to action is supported by recent estimates indicating significant morbidity and mortality directly attributable to loiasis [2][3][4][5][6]. A better understanding of the disease, as well as development of adequate diagnostics and appropriate treatment leading to improved patient care is needed [2][3][4][5][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study involving adult Bantu from two villages in the same region indicated microfilaremia prevalences of 27.7 and 29.5% [ 3 ]. Furthermore, a survey conducted in 2004 revealed Loa loa microfilaremia prevalences ranging from 7.5 to 50.8% across 15 villages [ 6 ].…”
Section: Introductionmentioning
confidence: 99%